An Experimental Application of Four Types of Chitosan Bead for Removal of Cationic and Anionic Pollutants - An, Byungryul; Choi, Jae-Woo (Kluwer Academic Publishers, 2019)
Four types of chitosan bead (CB) were tested to find the removal efficiency for cation and anion from solution. Hydrogel chitosan bead (HCB) was first prepared and then modified by chemical and physical treatment. Both the Cu(II) and phosphate removal were investigated based on the batch removal efficiency, a pH test, kinetics, and an isotherm test. For Cu(II) application, the highest Cu(II) uptake (approximately 83%) was obtained for the HCB; the modification by crosslinking by glutaraldehyde (GA) and air drying decreased this to approximately 60%, while phosphate removal was not affected by crosslinking and drying. Below pH 4.0, the removal efficiency of Cu(II) was decreased by approximately 20% for all type of CB, while phosphate uptake was determined by the type of CB, regardless of the initial pH. The maximum Cu(II) and phosphate uptake (Q) were 129 and 232 mg/g for the HCB and dried chitosan bead (DCB), respectively. The phosphate sorption rate was faster than Cu(II) at the beginning of the reaction for the hydrogel bead, while the dried bead reached the equilibrium in 72 h.